Chapter 5 The biology of entrepeneurship - Maged Nofal, Ahmed (SIOP Organizational Frontiers Series, 2021)
The Psychology of Entrepreneurship: New Perspectives is an update of the earlier landmark volume in the Society for Industrial and Organizational Psychology Organizational Frontiers Series. This new book takes stock of the advances in the field of the psychology of entrepreneurship with all new chapters and presents the latest findings on traditional topics, such as cognition, motivation, affect, personality, and action. The Psychology of Entrepreneurship: New Perspectives compiles research of the most prolific scholars in the field to produce an overview of the most important psychological topics relevant to entrepreneurship. It includes novel insights into topics such as entrepreneurial cognition, intrapreneurship and innovation, leadership, entrepreneurial competencies, action theory, entrepreneurship training, and the process of entrepreneurship. Additionally, the updated volume presents new topics that have become more and more important in entrepreneurship research. These topics include affect, clinical psychology and disorders, biological correlates of entrepreneurship, entrepreneurial teams, culture, identity, starting capital, failure and exit, contextual factors, age and demographic change, evidence-based entrepreneurship, and entrepreneurs' well-being. With a collection of authors comprising experts who have developed the field over the last decade, The Psychology of Entrepreneurship: New Perspectives is vital to all students, scholars, and instructors interested in staying abreast of the most current, novel research and insights into the psychology of entrepreneurship.